Nematicidal activity of four Piper species foliar extracts against Caenorhabditis elegans - Carmona-Hernández, Oscar; Martínez-Hernández, María de Jesús; Fernández, María del Socorro; Molina-Torres, Jorge; Ramírez-Chávez, Enrique; Barrientos-Salcedo, Carolina; Lozada-García, José Armando (Ecosistemas y Recursos Agropecuarios, 2022)
Piper spices haven showed a great biological potential as natural biocide, in different organism. This is attributed to the diversity bioactive metabolites present in tissue. In this research we evaluated the nematicidal activity of different foliar extracts from Piper spices against Caenorhabditis elegans. We evaluated the nematicide activity of the hy- droalcoholic, methanolic and ethanolic extracts. Chromatography prolife by HTPLC and GC-EIMS of the extracts with mayor activity was obtained. The ethanolic extract from Piper aduncum displayed higher activity as lethal concentration 50 (LC50) estimated at 0.650 mg mL−1. The bioactive metabolites identiﬁed were alkaloids, ﬂavonoids, terpenoids, steroids and coumarins. The GC-EIMS determinate 67 compounds in the higher activity extracts. Concluded the P. aduncum ethanolic extract has the higher activity and the mayor compounds diversity.